2018
DOI: 10.1097/qai.0000000000001806
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Fallible Men: Communication Strategies and Moral Issues in a Pre-exposure Prophylaxis Trial

Abstract: Based on the analysis of a French pre-exposure prophylaxis trial (Ipergay), and focusing on the communication strategies used to recruit volunteers, this article explores the figure who serves to justify the trial and who shapes the way in which populations concerned by this prevention tool are targeted. We show that this figure is that of the fallible man, a classic in moral philosophy: while aware of what is good or right for him, he is unable to put this knowledge into practice. The targeting of fallible me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Questions have also been raised as to whether PrEP may be reinforcing health inequities. Scholars have noted a paradox whereby the "ideal PrEP user" is also the "fallible man", someone simultaneously "vulnerable" to HIV acquisition by not having followed previous prevention guidelines but suddenly capable of complying with a complex prevention programme (Holt 2015;Trachman and Girard 2018). Individuals most at risk for HIV (such as those with serious mental health or substance use issues, insecure housing) may actually be deemed "too high risk" to adequately adhere to PrEP, while those with lower risk sexual practices for HIV may be more likely to be deemed eligible because they will be "good" (adherent) PrEP users (Auerbach and Hoppe 2015).…”
Section: Clinical and Epidemiological Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions have also been raised as to whether PrEP may be reinforcing health inequities. Scholars have noted a paradox whereby the "ideal PrEP user" is also the "fallible man", someone simultaneously "vulnerable" to HIV acquisition by not having followed previous prevention guidelines but suddenly capable of complying with a complex prevention programme (Holt 2015;Trachman and Girard 2018). Individuals most at risk for HIV (such as those with serious mental health or substance use issues, insecure housing) may actually be deemed "too high risk" to adequately adhere to PrEP, while those with lower risk sexual practices for HIV may be more likely to be deemed eligible because they will be "good" (adherent) PrEP users (Auerbach and Hoppe 2015).…”
Section: Clinical and Epidemiological Consequencesmentioning
confidence: 99%
“…The term 'MSM' finally makes sense as a market niche" (p. 945). Trachman and Girard (2018) have observed that early epidemiological discourse on PrEP often reified notions of the reckless GBM who is incapable of protecting himself from HIV without a biomedical fix, rather than "highlighting the exemplary nature of gay men who protect themselves" (p. S13). Thus, PrEP's success can overshadow decades of GBM safer sex cultures and community work done to prevent HIV (Dowsett 2009;Kippax et al 2013), and in so doing, it can also minimize how mainstream epidemiology directly fostered homophobia and HIV stigma by routinely problematizing GBM's sexual behaviour (Gaspar 2019).…”
Section: Sexual Politicsmentioning
confidence: 99%
“…Respectable gays present their sexual orientation as an accidental, non-essential, property of their personality; they do not take it to determine who they are. With gay marriage, the journey 27 For a critique of this rationalistic paradigm which leaves out gay experience, subjectivity, fantasy, sex and desire, see Adam (2011), Race (2012), Dean (2011Dean ( , 2012Dean ( , 2015aDean ( , 2015b, Halperin (2016), Trachman and Girard (2018). 28 In Germany, for example, there is a correlation between the growing political power of the homophobic right-wing populist party AfD, the rise of homophobic attitudes (LSVD n.d.; Decker and Kiess 2016, p. 51), and the rise of homophobic hate crimes (Beiker 2017), that many actors interpret as a causation (LSVD 2017).…”
mentioning
confidence: 99%